Effectiveness of Transport Guidelines on Intra Hospital Transport Practices of Nurses and Occurrence of Mishaps among Critically ill Patients (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Intrahospital transport means transporting ill patients for diagnostic and therapeutic procedureswith in the hospital. Implementation of intrahospital transfer demands a well organized meticulous planningand prompt application of well designed plan.Objectives: To compare intrahospital transportation practices and occurrence of mishaps during intrahospitaltransport before and after administration of hospital transport guidelines and to determine the associationwith situational variables (level of floors and distance of destination)Methods: Quasi experimental one group pre test post test design was used in the study by event sampling.55 pre test transport and 62 post test events were selected. IHT guidelines was given to nurses working inoperation theater by using demonstration cum lecture technique, one on one teaching provided to individualnurse consecutively. Observational technique was used for data collection Result showed that the meanpercentage of intrahospital practice were higher(89.37%) then pre test (40.03) with a mean difference of49.33. Computed t value (t=37.46,p=0.000) was statistically significant .Chi square value of occurrenceof mishaps regarding intrahospital transport is(X2 =53.9,p=0.001) statistically significant F value betweentransportation practices with distance from OT were(f=1.68,p=0.16) and Computed t value practices withlevel of floor were (t=1.60,p=0.39) statistically not significant at 0.05 level of significance. ConclusionIntrahospital transportation guidelines are effective in reducing mishaps and increases transportationpractices.
Keywords: Intra hospital transport practices, mishaps, transport guidelines